Effect Of Application Of Good Governance Principles On The Acceptance Of Zakat Funds In Amil Zakat Institutions In Medan City - Sri Rahayu; Saparuddin Siregar; Suginam Suginam; Azwansyah Habibie (Proceeding International Seminar of Islamic Studies, 2019)
Zakat is an obligation for every Muslim on his wealth that has reached haul and Nisab. Zakat is very potential as an effective means to empower the people's economy. Indonesia has a very large potential for zakat, data obtained from Baznas shows that the potential for zakat in 2017 reached 203 trillion rupiah but only 6.2 trillion rupiah was collected and classified as a minimum of its potential. This potential, if explored optimally from all Islamic societies and managed well with trustworthy management and high professionalism, will create a large amount of funds used to overcome the people's economy. The management of amil zakat institutions must be managed professionally with the application of the principles of good governance especially transparency and financial accountability which will generate public trust. This zakat research is very important to be tested and analyzed regarding the application of the principles of good governance principles that will affect the level of receipt of zakat funds. This type of research is quantitative that uses primary data by distributing questionnaires to 35 administrators of the Amil Zakat Institution. The hypothesis is tested by multiple linear regression. This study answers that partially the receipt of zakat funds is influenced by accountability but not influenced by transparency, while simultaneously transparency and accountability affect the receipt of zakat funds.